Pengaruh Tingkat Kepatuhan Wajib Pajak Badan TerhadapPenerimaan Pajak Yang Dimoderasi Dengan Pemeriksaan PajakPada Kpp Pratama Surakarta - Sukamto, Dian Maulida; , Drs. Muhammad Abdul Aris, M.Si (2016)
Receiving tax is one revenue for a country in order to pay expanses. In order to increase the income from taxes, government applies self assessment system hence that the compliance tax, are ready to be examined which therefore lead to tax audit. The purpose of the study is to analyze the influence of the corporate taxpayer compliance level against moderate tax revenue by tax audit. The population in the study is the corporate taxpayer registered with the Tax Office Pratama Surakarta. The method of determining the sample was purposive sampling method. The analysis methods used in this study were descriptive statical analysis and multiple linear regressions. The result showed that the compliance level Taxpayer Corporation and tax audit gave significant effect of the tax revenue. While the influence compliance level of the taxpayer corporation to tax revenue had been further weakened by the existing of the tax audit as a moderating variable.